The main lines of the State programme «Digital Kazakhstan» implementation - Kazbekov, T.B.; Romanko, Е.B.; Mussabekova, А.О.; Mukashev, T.A. (BUKETOV BUSINESS REVIEW, 2018)
The general trend of digital technologies development is disclosed. Their specification as one of the ways of national economy diversification, its reorientation from raw material industries to industrial-service model is given. It is proven that given program will allow to develop and approve new tools directed to modernization and digitalization of our enterprises with export orientation, as well as improving the quality of life of the population and economic competitiveness of Kazakhstan by means of progressive development of digital ecosystem. It is noted that program is directed to development of following areas: digital Silk way, creative society, digital transformations in the branches of economy, proactive state. It is emphasised that infrastructure, sufficient for a good start is created in Kazakhstan: basic level of digitalization is present in all branches of economy, the majority of the population has access to the Internet,electronic government is created and successfully functions.Innovative technologies and intelligent systems are considered, which will be introduced to key economic branches with the aid of digitalization of the branches of economy in order to ensure productivity growth and increase in the competitiveness on international level; as well as creation of innovative ecosystem, increase in the amount of technological start-up projects initiated in Kazakhstan and their capitalization. Feasibility of creation of Astana Hub international IT start-ups technology park, development of the Law «On venture financing» is justified; transition to digital state; creation of the centre of competence to digital industry; realization of projects to partial computer-aided manufacturing by introducing and modernization of the sensor system that will allow to increase significantly in productivity. It is concluded that program «Digital Kazakhstan» implies realization of the complex of interconnected measures for achievement of the key purpose - creation of innovative economy, entry into developed countries and transformation of the society and production , in order not to be left behind of modern technological world; integration of information systems of State authorities. The key to preservation of our economy competitiveness is development of digital component by joint efforts of the state and business.